Tangent delta extraction of cable joints for aged 11kV underground cable system - Permal N.; Chakrabarty C.K.; Avinash A.R.; Marie T.; Shafi Abd Halim H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cable jointing; Carbon; Carbon black; Extraction; Insulation; Systems engineering; Underground cables; Dissipation factors; Experimental approaches; Extraction method; High frequency alternating current; High frequency HF; Tangent delta; Trigonometric functions; Underground cable systems; Cables